2017
DOI: 10.1042/bsr20160643
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Fra1 expression by Wnt/β-catenin signalling promotes glioma aggressiveness through epithelial–mesenchymal transition

Abstract: Aberrant expression of Fos-related antigen-1 (Fra1) is commonly elevated in various malignant cancers and is strongly implicated in invasion and metastasis. However, the molecular mechanisms underlying its dysregulation in human glioma remain poorly understood. In the present study, we demonstrate that up-regulation of Fra1 plays a crucial role in the glioma aggressiveness and epithelial–mesenchymal transition (EMT) activated by Wnt/β-catenin signal pathway. In glioma cells, activation of Wnt/β-catenin signall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…For example, the MAPK signaling pathway, which mediates a series of physiological activities such as cell growth, development, differentiation, and apoptosis, is an important signaling pathway involved in carcinogenesis . The Wnt signaling pathway, related to the occurrence, proliferation, invasion, and transference of tumors, has great potential as both a marker for tumor diagnosis and target for cancer treatments . Besides, other pathways, such as the P53 signaling pathway, are also highly connected with tumor development .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the MAPK signaling pathway, which mediates a series of physiological activities such as cell growth, development, differentiation, and apoptosis, is an important signaling pathway involved in carcinogenesis . The Wnt signaling pathway, related to the occurrence, proliferation, invasion, and transference of tumors, has great potential as both a marker for tumor diagnosis and target for cancer treatments . Besides, other pathways, such as the P53 signaling pathway, are also highly connected with tumor development .…”
Section: Discussionmentioning
confidence: 99%
“…To study the mechanism underlying the GINS2 regulation of glioma growth, we examined the whole-gene expression profile 34,35 The Wnt signaling pathway, related to the occurrence, proliferation, invasion, and transference of tumors, has great potential as both a marker for tumor diagnosis and target for cancer treatments. 36,37 Besides, other pathways, such as the P53 signaling pathway, are also highly connected with tumor development. 38,39 Therefore, in order to verify these bioinformatics analysis results, we further assessed relevant cell cycle signaling pathways to determine their connection with GINS2.…”
Section: Discussionmentioning
confidence: 99%
“…Notch3 can increase the chemosensitivity in doxorubicin‐resistant breast cancer by negatively regulating Fra1. Fra1 has been shown to play an important role in EMT of colorectal cancer, ovarian cancer, glioma, and breast cancer cell lines . Fra1 was highly expressed in doxorubicin‐resistant breast cancer cells while Notch3 was underexpressed and this resistance was mediated by Fra1‐induced EMT.…”
Section: Breast Cancermentioning
confidence: 99%
“…It is unclear how CBR1 regulates EMT. In this study, it was found that CBR1 suppression stimulated the intracellular signaling pathways of TGF‐β and Wnt/β‐catenin (Table ), both of which have been reported to play roles in regulating EMT . The authors speculate that CBR1 regulates EMT by interacting with the TGF‐β and Wnt/β‐catenin pathways.…”
Section: Discussionmentioning
confidence: 76%